State of the union a marriage in ten parts - Hornby, Nick 1957- (Penguin Books, 2019)
"Married for years, Tom and Louise thought they had a stable home life-- until a recent incident pushed them to the brink. Going to therapy seemed like the perfect solution. But over drinks before their appointment, they begin to wonder: what if you take your marriage apart to see what's in there, but then you're left with a million pieces? For ten weeks, meeting before their weekly therapy sessions, their conversation forces them to look at their marriage-- and at each other."--Adapted from back cover
Keywords: Married people / England / Fiction; Couples therapy / Fiction; Man-woman relationships / Fiction; Couples therapy; Man-woman relationships; Married people; Domestic fiction; Fiction; England; Fiktionale Darstellung